The Effect of Audio Visual Learning Media on Student Learning Outcomes in Thematic Learning Theme I "Life in harmony" Subtheme 1 "Life in harmony at home": Pengaruh Media Pembelajaran Audio Visual terhadap Hasil Belajar Siswa pada Pembelajaran Tematik Tema I “Hidup Rukun” Subtema 1 “Hidup Rukun di Rumah” - Kiki Yunis Fika; Dr. Ida Rindaningsih, M.Pd (Academia Open, 2022)
This study aimed to examine the influence of audio-visual learning media on the learning outcomes of second-grade students in thematic learning at MI Darussalam Keboguyang, specifically focusing on the theme "Living in harmony" with the sub-theme "Living in harmony at home." The research utilized a quantitative experimental design known as the One Group Pretest-Posttest. The sample consisted of 30 students selected through purposive sampling. Data analysis involved a simple linear regression test conducted using SPSS 20 for Windows. The results revealed a significant positive effect of audio-visual learning media on the learning outcomes of second-grade students. The level of influence was determined to be 22.4%, indicating a fairly good impact based on the N-Gain test, which yielded a score of 62.7%. Overall, the findings support the effectiveness of audio-visual learning media in improving student learning outcomes in thematic learning. Highlights: The use of audio-visual learning media significantly improves student learning outcomes. Thematic learning in the context of "Living in harmony" at MI Darussalam Keboguyang. The study employs a quantitative experimental design to analyze the impact of audio-visual learning media on student learning outcomes. Keywords: audio-visual learning media, student learning outcomes, thematic learning, MI Darussalam Keboguyang, quantitative experiment